Factors Affecting the Management of Innovative English Language Teaching Methods at People’s Police Universities - Ân, Nguyễn Ngọc; Danh, Nguyen Duc (Advances in Social Sciences Research Journal, 2021)
Based on the theoretical basis of the factors affecting the management of innovative English teaching methods, the paper focuses on researching and investigating the current situation of factors affecting the management of innovative English teaching at People’s Police Universities to assess the importance and influence on management. The results of a survey with 49 leaders and 119 English language teachers at at People’s Police Universities showed the degree of influence factors ranging from quite to very influential and the importance of these factors all reach 100% from important or more across the sample. This result can be useful sources for administrators and lecturers to pay attention and propose measures to manage effectively in the innovative English teaching methods at People’s Police Universities.